Health Technology Assessment in the Context of Adaptive Pathways for Medicines in Europe: Challenges and Opportunities. Issue 6 (17th October 2016) - Bouvy, JC; Jonsson, P; Longson, C; Crabb, N; Garner, S
Abstract : Adaptive pathways for medicines have gained momentum and, in Europe, adaptive pathways have recently been introduced into the European Medicines Agency (EMA) processes after a successful 2‐year pilot. Although the concept, as initially proposed, contained several elements that would have required regulatory reforms, the adaptive pathways program has developed a more pragmatic scope (Box 1) .In this article, we explore the main challenges and opportunities adaptive pathways pose from a European health technology assessment (HTA) perspective .